The grapes of math : how life reflects numbers and numbers reflect life - Bellos, Alex, 1969- (New York : Simon & Schuster, 2014)
"From the bestselling author of Here's Looking at Euclid, a dazzling new book that turns even the most complex math into a brilliantly entertaining narrative. From triangles, rotations and power laws, to cones, curves and the dreaded calculus, Alex takes you on a journey of mathematical discovery with his signature wit and limitless enthusiasm. He sifts through over 30,000 survey submissions to uncover the world's favorite number, and meets a mathematician who looks for universes in his garage. He attends the World Mathematical Congress in India, and visits the engineer who designed the first roller-coaster loop. Get hooked on math as Alex delves deep into humankind's turbulent relationship with numbers, and reveals how they have shaped the world we live in"--
Includes bibliographical references (pages 304-322) and index.
Keywords: Mathematics -- Miscellanea; MATHEMATICS / General; SOCIAL SCIENCE / Anthropology / Cultural; MATHEMATICS / Essays; Mathematics; Miscellanea